1985
DOI: 10.1177/00220345850640121101
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Legionella-specific IgG and IgM Antibody in a Dental Clinic Population

Abstract: This study was undertaken to determine the frequency of Legionella infection in a dental clinic setting. Serum samples from 270 dental clinic personnel were evaluated using an enzyme-linked immunosorbent assay to detect Legionella-specific IgM and IgG antibodies. The pooled-species whole-cell-antigen preparation used in these assays was derived from six Legionella pneumophila strains and one strain each from Legionella bozemanii and Legionella micdadei. Significant levels of IgG and IgM antibodies were found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0
4

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 12 publications
(11 reference statements)
1
88
0
4
Order By: Relevance
“…11 Similar results were found in dental personnel working in a dental hospital in the USA. 12 No cases of Legionnaires' disease or Pontiac fever were reported amongst the study volunteers but unfortunately the DUWL were not tested for the presence of Legionellae. Presumably one would have expected to see heavy contamination of the system.…”
Section: Dentists' Legionella Serologymentioning
confidence: 96%
See 1 more Smart Citation
“…11 Similar results were found in dental personnel working in a dental hospital in the USA. 12 No cases of Legionnaires' disease or Pontiac fever were reported amongst the study volunteers but unfortunately the DUWL were not tested for the presence of Legionellae. Presumably one would have expected to see heavy contamination of the system.…”
Section: Dentists' Legionella Serologymentioning
confidence: 96%
“…10 It has been suggested that legionellae within DUWL may contribute to respiratory illness amongst the dental team. 11,12 The reported prevalence of legionellae in DUWL varies widely from 0-68% depending, in part, on the isolation procedures. [13][14][15] Variations in recovery rates are seen with different geographic locations, presence of large cold-water tanks and complex plumbing systems, 7 thermal conditions and the type of dental equipment.…”
Section: N B R I E Fmentioning
confidence: 99%
“…28 Dentists' health would also seem to be directly at risk. [29][30][31] The American Dental Association (ADA) is concerned about these problems and adopted a statement on December 13, 1995, identifying it as one of the critical research areas in dentistry today. 25 The ADA set a number of less than 200 colony forming units per millilitre as the goal to be reached by all members by the year 2000.…”
Section: Research Cross Infectionmentioning
confidence: 99%
“…In similar studies carried out in the USA, 20% of West Virginia students and staff of dentistry department were found to be positive in terms of antibodies in their serum (7). These studies indicate the increased risk of exposure of dentistry personnel to pathogenic gram positive and negative bacteria and that the dental unit waterlines can be the source of infection.…”
Section: Discussionmentioning
confidence: 67%